2019
DOI: 10.1161/circheartfailure.119.006218
|View full text |Cite
|
Sign up to set email alerts
|

Survival Outcomes After Heart Transplantation

Abstract: Background: Currently, women represent <25% of heart transplant recipients. Reasons for this female underrepresentation have been attributed to selection and referral bias and potentially poorer outcomes in female recipients. The aim of this study was to compare long-term posttransplant survival between men and women, when matched for recipient and donor characteristics. Methods and Results: Using the International Society for Heart an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 24 publications
6
46
0
5
Order By: Relevance
“…Our analysis did not find the effects of gender a be significant predictors of long‐term survival, similar to that of previous report 6 . Furthermore, sex‐mismatch was also insignificant.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our analysis did not find the effects of gender a be significant predictors of long‐term survival, similar to that of previous report 6 . Furthermore, sex‐mismatch was also insignificant.…”
Section: Discussionsupporting
confidence: 90%
“…Along with these findings, there are few existing pretransplant recipient and/or donor features that have been found to have a long‐term impact on survival. In previous studies, recipient gender, use of prior cardiac assist as a bridge to transplantation, and/or certain donor characteristics, such as traumatic brain injury versus other etiology of death, have not shown to be influential on midterm (5–10 year) survival after OHT 5–8 . However, black race has been shown to have negative association with longer‐term survival 9 .…”
Section: Introductionmentioning
confidence: 96%
“…Heart transplant (HT) is the gold standard of treatment for selected heart failure (HF) patients refractory to optimal therapy with poor prognosis in the absence of significant comorbidities 4–6 . Although much research has been done to study different aspects of HT, gender differences have received little attention so far 7–9 and most studies have mainly addressed donor–recipient matching 10–12 . It is necessary to have reliable information on the differences in HT by gender and to identify gaps in knowledge and needs of prospective studies.…”
Section: Introductionmentioning
confidence: 99%
“… 76 , 77 , 78 Currently, female recipients only represent 1 in 4 heart transplants worldwide, and appear to receive hearts from higher risk donors. 79 This has been ascribed to women presenting with end-stage heart failure at an older age, selection, referral bias, and purported poorer outcomes in female recipients. 80 , 81 , 82 Female recipients, however, have significantly higher post-transplant survival than men (median 12.2 years versus 11.4 years, respectively).…”
Section: Updates In Heart Transplantationmentioning
confidence: 99%
“…Both concluded that, when matched for recipient and donor characteristics, sex was not a significant variable predicting mortality in early post-operative, constant, or late survival of heart transplantation. 71 , 79 …”
Section: Updates In Heart Transplantationmentioning
confidence: 99%